Interpersonal dynamics to approach chronic pain in late adulthood: An overview of the state-of-the-art - Matos, M. (Ispa Psychology & Pain Management – Psychological management of pain: a state-of-the-science update, 2022)
As people age, chronic pain becomes highly prevalent (50% in community settings and more than 85% in institutional settings) translating into an obstacle to healthy ageing, by preventing people from independently do activities of daily living and to engage in social interactions. Therefore, investment on social support networks, professionals and care provision is a key path to reduce disabilities in ageing populations with chronic pain. We have proposed that pain-related social support might be protective or a risk factor, as far as it promotes functional autonomy vs dependence (the extent to which people are able to perform activities of daily living with or without assistance). Through quantitative (cross-sectional and longitudinal) and qualitative methods, we have concluded that promoting functional autonomy is identified by older adults as the most helpful and enabling type of support. Also, it has shown to have a double protective role of the detrimental effects of pain intensity on pain disability. Concerning the promotion of functional dependence, our findings confirmed it is a risk factor. Since it predicted an increase in older adults’ pain-related disability, after 3 months, by decreasing their level of physical functioning and of self-efficacy.